1991
DOI: 10.1016/0002-9149(91)90488-7
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic therapy in patients requiring cardiopulmonary resuscitation

Abstract: Cardiopulmonary resuscitation (CPR) is often considered a contraindication to thrombolytic therapy for acute myocardial infarction. Of 708 patients involved in the first 3 Thrombolysis and Angioplasty in Myocardial Infarction trials of lytic therapy for acute infarction, 59 patients required less than 10 minutes of CPR before receiving lytic therapy (CPR greater than 10 minutes was an exclusion of the trials) or required CPR within 6 hours of treatment. The patients receiving CPR were similar to the remainder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

1992
1992
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 13 publications
1
24
0
4
Order By: Relevance
“…In the nonthrombolysis group we observed major bleeding complications in seven of 133 patients (5%, 95% confidence interval 1-9%) (patient nos [14][15][16][17][18][19][20]. In patient 14 (CPR duration 12 min) the X-ray revealed left-sided fluidopneumothorax without signs of tension as major complication.…”
Section: Patients With Major Bleeding Complicationsmentioning
confidence: 89%
See 2 more Smart Citations
“…In the nonthrombolysis group we observed major bleeding complications in seven of 133 patients (5%, 95% confidence interval 1-9%) (patient nos [14][15][16][17][18][19][20]. In patient 14 (CPR duration 12 min) the X-ray revealed left-sided fluidopneumothorax without signs of tension as major complication.…”
Section: Patients With Major Bleeding Complicationsmentioning
confidence: 89%
“…In a retrospective analysis, Tenaglia et al [18] studied 59 patients after short duration of CPR (<10 min), 37 of whom required only defibrillation, excluding patients with a resuscitation procedure lasting more than 10 min They found no direct complications of thrombolytic therapy and concluded that thrombolytic treatment after short duration of CPR is safe and effective. Weston and Avery [20] found three significant bleeding complications after thrombolysis in a group of 16 patients, all of these patients survived to hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two series comprising a total of 102 patients treated with CPR for durations ranging from 4 -120 min, however, found no increased incidence of major or minor bleeding complications [33,34]. Thus, in the absence of obvious chest wall trauma or anoxic brain injury (the latter would theoretically increase the risk of intracranial hemorrhage), CPR should not be considered a contraindication to thrombolysis.…”
Section: Cardiopulmonary Resuscitationmentioning
confidence: 99%
“…O consenso até o momento é de que se a ressuscitação cardiopulmonar foi de curta duração e aparentemente atraumática, o medicamento pode ser administrado. Alguns relatos de administração de trombolíticos na parada cardiorrespiratória após infarto do miocárdio ou embolia pulmonar maciça têm evidenciado resultados animadores, mesmo III Diretriz sobre Tratamento do Infarto Agudo do Miocárdio quando essa terapêutica é utilizada como recurso extremo após falha nas medidas habituais e com ressuscitação prolongada [654][655][656][657][658][659][660][661] . A possível explicação para os efeitos benéficos é que, ao lado de sua ação no processo causal, dissolução do trombo coronariano e/ou de êmbolo arterial pulmonar, haveria incremento da reperfusão na microcirculação, principalmente em território cerebral 662 , como demonstram estudos experimentais 663 , o que permitiria a recuperação com menor dano cerebral.…”
unclassified